(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Multi-field coupling simulation method based on the physical principles is used to simulate the discharge characteristics of nanosecond pulsed plasma synthetic jet actuator. Considering the effect of the energy transferring for air, the flow characteristics of nanosecond pulsed plasma synthetic jet actuator are simulated. The elastic heating sources and ion joule heating sources are the two main sources of energy. Through the collisions, the energy of ions is transferred to the neutral gas quickly. The flow characteristics of a series of blast waves and the synthetic jet which erupt from the plasma synthetic jet (PSJ) actuator are simulated. The blast wave not only promotes outward, but also accelerates the gas mixing the inhaled gas from the outside cavity with the residual gas inside the cavity. The performances of PSJ actuator fluctuate in the first three incentive cycles and become stable after that.